Identification of Science Process Skills of Group B Students at Kreativa Gebang Kindergarten - Ni Luh Putu Nina Sriwarthini; Nurhasanah Nurhasanah; I Made Suwasa Astawa (Jurnal Penelitian Pendidikan IPA, 2024)
The newest Curriculum stipulates a scientific approach as a characteristic of the national PAUD curriculum. In reality, kindergartens still have not optimized this. Therefore, it is necessary to identify the science process skills of early childhood students so that improvements can be made immediately. This research aims to identify and analyze the science process skills of Group B Students at Kreativa Gebang Kindergarten. This is descriptive research. The research instruments used were video recordings of learning activities, observation sheets for learning activities, and student development assessment reports (LPPA). The data obtained in this research was analyzed using a combination of analysis (quantitative – and qualitative). The results showed: 1) The identified science process skills of Group B students were observing, classifying, and communicating skills; 2) The percentage of achievements in observing skills that were categorized into developing very well (BSB) categories were 41.4%, Classification skills were at 32.8%, and communication skills were at 14%. Based on the data, it can be concluded that the science process skills of group B students at PAUD Kreativa Gebang were still relatively low because the percentage of achievements in the three science process skills that were categorized into developing very well (BSB) categories was below 50%.